Pengaruh Pelatihan dan Lingkungan Kerja Terhadap Kinerja Guru di Kabupaten Bandung (Studi Kasus pada Guru SMP Islam Pacet) - Yayu Purnama Dewi; Wandi Kurniadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The quality of education is highly dependent on teacher performance, which is influenced by various internal and external factors. This study aims to analyze the influence of training and the work environment on teacher performance at SMP Islam Pacet, Bandung Regency. Using a quantitative descriptive and verificative approach, data were collected through a census of 40 teachers. Data analysis was performed using multiple linear regression with SPSS 25. The results indicate that both training and the work environment significantly and positively influence teacher performance, both partially and simultaneously, with a determination coefficient ($R^2$) of 80.1%. These findings suggest that systematic training and a conducive work environment are essential for maintaining professional teaching standards.